Postnatal outcomes of infants affected by rhesus hemolytic disease in a tertiary care center in Northern India - Naranje, Kirti M; Malik, Richa; Singh, Anita; Poddar, Banani; Pradhan, Mandakini; Gupta, Girish (Indian Journal of Child Health, 2019)
Background: Advances in prenatal and postnatal care of neonates with rhesus hemolytic disease of the newborn (RHDN) have led to improved outcomes. Studies evaluating the postnatal outcomes in rhesus (Rh) isoimmunized infants from developing countries are limited. Objective: The objective of this study was to evaluate the postnatal outcomes of neonates ?32 weeks gestation with RHDN. Methods: A prospective observational study was conducted from July 2014 to June 2016 in a tertiary care neonatal unit in North India. Neonates affected by RHDN were managed as per the standard protocol and were followed up for the first 6 months of life. Primary outcomes were the duration of phototherapy (PT), need for exchange transfusion (ET), occurrence of late-onset anemia, and need for top-up transfusions. Results: A total of 33 newborns with RHDN were included in the study. Median duration of PT was 138 h (interquartile range 64–188) and was inversely correlated with intrauterine transfusion number (Spearman correlation coefficient ?0.46; p=0.02). Of 33 neonates with RHDN, 14 (42.4%) neonates required ET. Late-onset anemia was seen in 25 (75.7%) neonates and 17 (51.5%) required at least one top-up transfusion. Cholestasis was seen in 5 (15.1%) neonates. Conclusions: Despite advances in care, short-term morbidities in neonates affected by RHDN are common and require intensive management.